THE POTENTIAL OF ISLAMIC BANKING IN THE INDONESIAN ECONOMY - Annisa Salsabila Safiah; Nadiah Rabbaniah; Muhammad Misbakhul Munir (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Islamic banking has the potential to have a significant impact on the Indonesian economy, by offering sharia-compliant financial solutions that promote financial inclusion and support the growth of small and medium enterprises (SMEs). This study aims to explore the potential of Islamic banking in the Indonesian economy by looking at its historical development, current status, and future prospects. The research methods used include a comprehensive literature review, case studies on the role of Islamic banks in financing SMEs, and an analysis of the regulatory and policy environment for Islamic banking in Indonesia. The findings reveal that the Islamic banking sector in Indonesia has experienced impressive growth, with financing growth surging by 18.8% in 9M22. However, the adoption of Islamic banking in the MSME sector is still relatively low, mainly due to the novelty of Islamic financial institutions and the weakness of MSMEs in meeting Islamic financing requirements. The research also highlights the role of Islamic finance in promoting financial inclusion, deepening financial inclusion not only by providing Shariah-compliant products to the Muslim community, but also by meeting the needs of the underserved Muslim community. The study emphasizes the importance of policy reforms and regulatory support in driving the growth of Islamic banking in Indonesia. In conclusion, the potential of Islamic banking in the Indonesian economy is considerable, offering valuable opportunities to promote financial inclusion and support SME growth. However, to fully capitalize on this potential, Islamic banks and financial institutions need to address the challenges and limitations that currently prevent them from effectively serving the MSME market.